A meta-analysis of the effect of peer tutoring in Science, Technology, Engineering and Mathematics (STEM) subjects - Hidayat, Riyan; Mohd Saad, Mohd Rashid (Elsevier, 2025)
Currently, researchers have started to become interested in studying the impact of peer tutoring on academic achievement. Based on cognitive constructivism ideas. peer tutoring, founded on focuses on the significance of social interactions in learning and how they influence children's cognitive development. As such, this meta-analysis aims to look into the overall effect of peer tutoring, emphasising on STEM disciplines. The researchers utilised the PRISMA procedure to conduct a literature search across resources such as Web of Science, Scopus, and Google Scholar. The process yielded 24 works with 3311 participants. The researchers calculated the effect size with standardized mean differences (SMD) and 95 % confidence interval using the R software packages. The results indicated that peer tutoring has a significant effect on academic achievement (effect size [ES] = 1.23, 95 % confidence interval [CI] [0.75, 1.70], p < 0.001) and other learning outcomes (effect size [ES] = 0.40, 95 % CI [0.20, 0.59], p < 0.001). The subgroup analysis showed revealed substantial changes in effect sizes between subjects; however, no significant differences by the type of peer tutoring were found. Thus, this suggests that studying this effect has the potential to significantly improve academic performance, specifically in STEM fields.